THE RELATION OF NORTH ATLANTIC OSCILLATION(NAO) AND ENSO WITH PRECIPITATION IN THE SOUTHERN SHORES OF CASPIAN SEA - Zahra Hejazizadeh; Mehry akbary; Zarin jamshidiyini (تحقیقات کاربردی علوم جغرافیایی)
The present study investigated the impacts of NAO and ENSO on the precipitation in the southern shores of Caspian Sea. The accumulated monthly and annual rainfalls from 5 synoptic stations during the years (1956-2017) were taken through Islamic Republic of Iran Meteorology Organization (IRIMO) and the Multivariate Enso Indices (MEI) and NAO activity years are obtained from National Oceanic Atmospheric Administration. Pearson correlation was used to investigate the relationship between indices and precipitation amounts of selected stations. The results showed that there was a significant relationship between precipitation and NAO index in some months in all stations but this correlation was not following a particular pattern in all the stations. The maximum correlations were observed at Babolsar and   Anzali station and the least correlation was found at  Gorgan stations. The correlation between precipitation and different phases of NAO showed that there was a positive correlation between precipitation and negative phase of the index in Ramsar station and a negative correlation between precipitation and positive phase in the Gorgan station.The results of the Pearson correlation show a significant correlation between the MEI and rainfall amounts in the autumn in some stations in the early winter. In Review drought and wet periods with both Indicator it was observed that the behavior of the stations in the El Niño period, which was with different phases of the NAO was not entirely harmonious but the coefficient of 89% of rainfall in normal and more than normal during the period of El Niño showed that Elnino is better fitted to normal and more than normal rainfall in these stations also coefficient of 60%  of weak to severe droughts in the Lanina period in the selected stations Indicates that the LaNina phase was more related with severe droughts in the under studied period.